Analisis Ekspor Kopi Indonesia ke Malaysia: Peluang Perdagangan Kopi Antar Negara - Raharjo, Bagas Putra; Asmara, Kiky (Jurnal Ilmiah Wahana Pendidikan, 2023)
This journal article analyzes the potential and barriers of Indonesian coffee exports to Malaysia in the context of the ASEAN Economic Community. Since 1993, ASEAN has implemented free trade among its members through the Common Effective Preferential Tariff (CEPT), gradually reducing tariffs to zero percent, except for sensitive and highly sensitive goods. In 2010, CEPT was replaced by the ASEAN Trade in Goods Agreement (ATIGA), which aims to eliminate tariff exceptions for all goods. The ASEAN Economic Community Blueprint, signed in 2007, aims to make ASEAN a single market and production base, a competitive economic region, and a fair economic development area for the flow of goods, services, investments, labor, and capital. This article highlights Indonesia's role in foreign trade with Malaysia, focusing on the barriers and potential for cooperation in the agricultural sector, particularly in Indonesian coffee exports to Malaysia. The article also discusses the positive impact of coffee development on the Indonesian economy, involving approximately 1.96 million farmer households. The analysis indicates that coffee is a highly potential commodity, and Indonesian exports to Malaysia have significantly increased in recent years, indicating great opportunities for Indonesia to send its superior products to Malaysia.